PERAN KKN TEMATIK ERA COVID 19 MENAMBAH KREATIFITAS MAHASISWA DAN MASYARAKAT DALAM MEMBUKA WISATA KULINER ÃƒÂ¢Ã¢â€šÂ¬Ã…â€œDESA PETASANÃƒÂ¢Ã¢â€šÂ¬Ã‚Â DI DUSUN SIMBAR DESA TAMPO - Atiqatul Musyarofah; Mufidah Yusroh; Nurul Fatimah (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2021)
KKN is one of the activities with some knowledges and deals with many sectors. So that, the approach used were interdisciplinary and cross sectors. The KKN place used for dedication of Ibrahimy students was in Petasan, Simbar Tampo. This place was no culinary place before. Mr. Sugeng and Juari as founder of this culinary place and also they are as socialite in this village who had an idea in forming this culinary place after the Ibrahimy’s students came to this place. This culinary place was formed in August 12th 2021. Some Banyuwangi societies were still be a creative society in arising culinary destination eventhough the Covid pandemic still exist. It was as done by some younger community in three villages in Purwoharjo and Cluring which also made culinary place that was Kali Kurung. This culinary place located in the side of Simbar river that is in between of two districts, Purwoharjo and Cluring. This place was by the dense of the bamboo trees along the river. The visitors can enjoy several foods made from trout such as wader, catfish, tombro, bawal, and sodat. This destination is managed by the young community as Petasan (Pemuda Perbatasan). Besides, this program is eefcetive for Ibrahimy students who implemented KKN as their program that was directly deal with society and it would be the meaningful program ever for them.